(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
As a way to ensure survival, companies seek to optimize their sources of funding to guarantee resources for the operation of their businesses. The image to the market is an asset that needs to be properly communicated to the effectiveness of firm strategies. Funders / investors, on the other hand, are looking for information to assist them in making investment decisions. Often, reputational guides present themselves as theoretical subsidies for the market. In the present study, the aim was to verify whether the presence or not in these guides, especially in guides on the quality of the work environment provided to workers, interferes in the investors’ decisions. The research strategy was based on the use of an experiment with a between-subjects approach, in which there was the manipulation of an independent factor, namely, the presence or not of reputational guides. The research was applied with undergraduate students from public universities, on a voluntary basis, and there was no incentive for participation. For statistical analysis, Correspondence analysis was used as exploratory technique and Multinomial Logistic Regression as confirmatory technique. The results showed that the presence in guides does not influence investment decisions, which suggests that investors reasonably well informed about possible organizations to invest do not take such information as a decisive factor to invest.